Rapid Detection of Foodborne Pathogen Bacteria Vibrio parahaemolyticus in Seafood Using Gene ToxR with Real-Time Polymerase Chain Reaction Method - Ismaya Krisdawati; Muktiningsih Nurjayadi; Jefferson Lynford Declan; Gladys Indira Putri; Dandy Akbar Juliansyah; Maharani Azka Azzahra; Irvan Maulana; Irma Ratna Kartika; Vira Saamia; Dwi Ana Oktaviani; I Made Wiranatha; Hesham Ali Al-Enshashy (Microbiology Indonesia, 2023)
Cases of food poisoning often occur due to food contamination caused by pathogenic bacteria. One of the pathogenic bacteria is Vibrio parahaemolyticus which is found in seafood. Thus, a fast, accurate and specific detection method is needed. The purpose of this study was to quickly detect Vibrio parahaemolyticus bacteria in seafood samples targeting the ToxR gene using Real Time PCR. In a previous study, gradient PCR was used to optimize ideal annealing temperature ranges from 53-62°C and revealed that 58°C produced the best outcomes for the ToxR primer with a size of 171 base pairs. Real-Time PCR was utilized to amplify, specify, and test for sensitivity under the ideal conditions from the PCR Gradient. The confirmation results show that the primer pairs could amplify ToxR of Vibrio parahaemolyticus with the amount of concentration as much as 50 ng/µL with Ct 10,69 and 10,32 and melting curve at temperature 82,18°C and 82,23°C. This primer pair can also distinguish non-target bacteria with different Ct and melting curve temperature. The sensitivity assay for this primer can amplify DNA templates at concentration 0,0032 ng/µL. Shrimp samples that are contaminated artificially can still be detected at Ct 13,02 and Ct 13,09. Based on these results, it can be concluded that Real Time PCR with ToxR primer can be applied to develop a detection kit for Vibrio parahaemolyticus in seafood.